338 Autonomic function and hyper-adrenergic tone despite beta-blockers in chronic coronary syndrome with preserved ejection fraction: prevalence and related factors. (8th December 2021) - Italia, Antonio; Lazzeroni, Davide; Moderato, Luca; Centorbi, Claudio; Bini, Matteo; Magnani, Giulia; Castiglioni, Paolo; Brambilla, Lorenzo; Piepoli, Massimo; Coruzzi, Paolo; Niccoli, Giampaolo; Ardissino, Diego
Abstract: Aims: Autonomic dysfunction is a prevalent and independent risk factor for adverse cardiovascular events and mortality in chronic coronary syndrome (CCS). Beta-blockers (BB), directly inhibiting adrenergic receptors, have been associated with a significant reduction in mortality and/or cardiovascular events in patients with recent acute coronary syndrome (ACS) or in those with heart failure (HF) with reduced left ventricular ejection fraction (LV-EF); on the other hand, the protective benefit in CCS patients without prior ACS or HF is less well established and lacks placebo-controlled trials. The aim of the study was to investigate the prevalence of hyper-adrenergic tone in CCS with preserved LV-EF in patients with or without BB as well as to assess related factors of hyper-adrenergic tone despite BB. Methods: A total of 165 consecutive CCS patients have been enrolled. Inclusion criteria were documented coronary artery disease and preserved left-ventricular ejection fraction (>50%). Exclusion criteria were: recent ACS (<6 months), HF symptoms (NYHA >1) and atrial fibrillation. According to Heart rate variability (HRV) guidelines, 5 min beat-to-beat analysis was performed in order to assess sympatho-vagal balance (without BB wash-out). Patients were then divided into in two groups: hyper adrenergic tone (LF/HF > 2.01) and normal adrenergic tone (LF/HF < 2.01). Moreover, patients with hyper-adrenergic tone despite BB were classified as 'BB non-responders' while patients with normal adrenergic tone as 'BB responders'. Results: Mean age was 64 ± 12 years and male gender was prevalent (75%). Patients treated with BB were 56% and the majority (96%) were treated with high selective. Overall hyper adrenergic tone (isolated or associated with blunted vagal tone) was found in 47% of CCS patients and no difference was found in the percentage of hyper-adrenergic tone between patients with or without beta-blockers (45% vs. 55% P  = 0.716). Within the BB groups, 89% had heart rate at target (<70 b.p.m.), while only 11% showed heart rate not at target (>70 b.p.m.). Among the heart rate not at target 80% had hyper-adrenergic tone despite beta-blockers (non-responders); on the other hand, among the heart rate not at target hyper-adrenergic tone despite beta-blockers was found in 43%. No differences in types of BB (metoprolol vs. bisoprolol) between BB responders and non-responders was found ( P  = 0.714). Higher left atrial volume index (36 ± 8 vs. 42 ± 14; P  = 0.029) and E/e' ratio (an echocardiographic marker of high left ventricular filling pressure) (9.4 ± 2.1 vs. 7.4 ± 2.1; P  = 0.038) were found in patients with hyper-adrenergic tone despite beta-blockers (non-responder). Moreover, a trend toward significance of higher Lown's arrhythmic risk was found in non-responders (19% vs. 8%; P  = 0.066) (Figure). Finally, Beta-blockers patients with bradycardia and hyper-adrenergic tone (non-responders) had higher prevalence of carotid artery disease (64% vs. 44%; P  = 0.047), where baroreceptors are located. Conclusion: The prevalence of hyper-adrenergic tone is high in CCS patients with preserved ejection fraction; about half of patients treated with beta-blockers had residual hyper-adrenergic tone (non-responders). Hyper-adrenergic tone in BB patients is higher in those with 24-h heart rate not at target (>70 b.p.m.), thereby suitable of BB titration, as well as in those with diastolic dysfunction or with carotid artery disease, where baroceptors are located.